La rivalité commerciale entre les éditeurs d’estampes français et flamands en Espagne: le témoignage de Jusepe Martínez (1669-1677) - Jiméno Solé, Frédéric (In Monte Artium, 2010)
Abstract During the years 1600 — 1630 there was extensive trade between France and Spain. The Spanish economy prospered because of the resources, provided by her overseas colonies in America. Small goods, among which prints, supplemented the cargos that were shipped from Sevilla to the New World. Besides, lots of engravings from France were sold to Spanish tradesmen who supplied the various local markets (Valencia, Sevilla, Madrid, Cordoba, Granada, Barcelona, Valladolid, Saragossa and Toledo). The Parisian print publishers Nicolas Mathonière, Simon Donget, Jean Le Clerc IV and their fellow publishers regularly closed business deals with Spanish merchants (e.g. Sébastien Carlet, Miquel Rosset, Antoine Sobrier, Barthélemy Liousse). The trade agreement could cover three dozen to no less than 17,000 prints. These large quantities of prints consisted of cheap copies of ‘old-fashioned’ Flemish prints from the end of the 16th century (after Maarten de Vos for example), prints after French or Italian designs, small devotional prints and portrait engravings. The clientele — existing mostly of religious orders and other pious people — had no great demands on the artistic quality of the prints they bought. We shift the attention of the international trade in prints and wide dissemination of visual imagery, to produce units of prints. By focusing on workshops of engravers, professional relationships between members of such an enterprise become clearer. Moreover, one gets insight in the changes of publishing funds over the years.